Rôle des environnements dans les origines et l’évolution de la bipédie chez les hominidés : exemple des zones boisées sèches de l’Afrique - Brigitte Senut (Revue de Primatologie, 2022)
In the literature, reference has often been made to the environments in which our ancestors lived, emphasizing dietary requirements and/or the importance of behaviours in these more or less wooded environments. However, few studies have been done on the structures of the environment and their impact on the origin of bipedalism. Whereas open savannah is no longer recognized as a good original environment in which bipedal locomotion emerged, dry forests deserve more attention and the structure of the Miombos woodland offers an interesting possibility of throwing light on the acquisition of erect bipedalism. This category of vegetation is composed of large trees with vertical trunks distant from each other, which may have favoured a mixed locomotion associating bipedalism and climbing in the ancestors of Australopithecines and humans. These precursors, different from chimpanzees and humans in their anatomy and proportions, climbed trees in different ways, probably without a hallux as divergent as that of chimpanzees. In Miombo woodland, accessing arboreal food resources frequently requires going across the ground from tree to tree. In addition, they must also have diversified their diet according to seasonality and perhaps they added other tougher elements to their diet as well. It is suspected that the Miombo woodlands, the northern limit of which is northern Tanzania, were more widespread during the Miocene and were therefore widespread in areas where the first hominids (here restricted to Homo and his forerunners) have been found.